2-Aminoadipic acid protects against obesity and diabetes. Issue 2 (November 2019) - Xu, Wang-Yang; Shen, Yan; Zhu, Houbao; Gao, Junhui; Zhang, Chen; Tang, Lingyun; Lu, Shun-Yuan; Shen, Chun-Ling; Zhang, Hong-Xin; Li, Ziwei; Meng, Peng; Wan, Ying-Han; et al.
Abstract : Obesity and type 2 diabetes (T2D) are both complicated endocrine disorders resulting from an interaction between multiple predisposing genes and environmental triggers, while diet and exercise have key influence on metabolic disorders. Previous reports demonstrated that 2-aminoadipic acid (2-AAA), an intermediate metabolite of lysine metabolism, could modulate insulin secretion and predict T2D, suggesting the role of 2-AAA in glycolipid metabolism. Here, we showed that treatment of diet-induced obesity (DIO) mice with 2-AAA significantly reduced body weight, decreased fat accumulation and lowered fasting glucose. Furthermore, Dhtkd1 −/− mice, in which the substrate of DHTKD1 2-AAA increased to a significant high level, were resistant to DIO and obesity-related insulin resistance. Further study showed that 2-AAA induced higher energy expenditure due to increased adipocyte thermogenesis via upregulating PGC1α and UCP1 mediated by β3AR activation, and stimulated lipolysis depending on enhanced expression of hormone-sensitive lipase (HSL) through activating β3AR signaling. Moreover, 2-AAA could alleviate the diabetic symptoms of db/db mice. Our data showed that 2-AAA played an important role in regulating glycolipid metabolism independent of diet and exercise, implying that improving the level of 2-AAA in vivo could be developed as a strategy in the treatment of obesity or diabetes.